Bioenergetic and Metabolic Adaptation in Tumor Progression and Metastasis - Herst, Patries M.; Carson, Georgia M.; Eccles, David A.; Berridge, Michael V. (Frontiers in Oncology, 2022)
The ability of cancer cells to adjust their metabolism in response to environmental changes is a well-recognised hallmark of cancer. A diverse array of cancer and non-cancer cells within individual tumors compete for metabolic resources. Metabolic demands change dynamically during tumor initiation, progression and metastasis, challenging our quest to better understand tumor biology and develop novel therapeutics. Vascularization, physical constraints, immune responses and genetic instability promote tumor evolution resulting in immune evasion, opportunities to breach basement membrane barriers and spread through the circulation and lymphatics. In addition, the unfolded protein response linked to the ubiquitin proteasome system is a key player in addressing stoichiometric imbalances between nuclear and mitochondrially-encoded subunits of respiratory complexes, and nuclear-encoded mitochondrial ribosomal protein subunits. While progressive genetic changes, some of which affect metabolic adaptability, contribute to tumorigenesis and metastasis through clonal expansion, epigenetic changes are also important and more dynamic in nature. Understanding the role of stromal and immune cells in the tumor microenvironment in remodeling cancer cell energy metabolism has become an increasingly important area of research. In this perspective, we discuss the adaptations made by cancer cells to balance mitochondrial and glycolytic energy metabolism. We discuss how hypoxia and nutrient limitations affect reductive and oxidative stress through changes in mitochondrial electron transport activity. We propose that integrated responses to cellular stress in cancer cells are central to metabolic flexibility in general and bioenergetic adaptability in particular, and are paramount in tumor progression and metastasis.